(untitled) (Development Service Industry Management, 2025)
The article is devoted to the study of the key role of higher education in achieving sustainable development goals. It is found that education is one of the key prerequisites for the implementation of the 2030 Agenda for Sustainable Development. The roles that higher education performs within each component of sustainable development (economic, social and environmental) are determined. The provisions that should become a guide on the path to the transformation of education for sustainable development are studied. It is determined that the modern global concept of education is aimed at forming in young people the abilities and skills to live in a complex multicultural and rather unpredictable world, developing important competencies, including: systems thinking for understanding complex socio-economic systems; critical thinking and the ability to predict and assess the consequences of one’s own actions and deeds; the ability to interact with people and the environment, understanding and respecting the needs of others; self-awareness, including environmental awareness, understanding one’s own role in society; the ability to develop and implement innovative ideas for sustainable development; understanding the meaning and support of the values and goals of sustainable development; the ability to make rational decisions that contribute to sustainable development, etc. The article outlines the third mission of universities, the importance of which lies in the support of higher education institutions for socially oriented education aimed at forming in students the knowledge and skills of a responsible attitude and solving socially important problems, by integrating the efforts of science, business, government and the public.